Border socioeconomic crisis: a view from the sustainable development goals in a binational border context - Jaimes Méndez, Nora Marcela (Ingeniería Solidaria, 2025)
Introduction: This research is the outcome of a postgraduate master’s thesis conducted in the municipality of Villa del Rosario in 2020. Objective: The study aims to describe the socioeconomic crisis in the border region from the perspective of the Sustainable Development Goals (SDGs), triggered by the unilateral closure of the border by the Venezuelan government, focusing on the Municipality of Villa del Rosario, Colombia. Methodology: A quantitative, exploratory, descriptive, and inferential approach was adopted. Stratified sampling was employed, and data were collected through the administration of a social survey. Results: The analysis revealed precarious socioeconomic conditions among the population, particularly concerning housing quality and access to public services. Conclusion: While the deep historical ties among residents are evident, it is necessary to move beyond a state-centric vision of public policies toward a more balanced development model that involves diverse civil society actors. Originality: This master’s thesis emphasizes the significance of the border zone, its unique dynamics, and the challenges that negatively impact the quality of life of inhabitants in this shared binational region.